2021
DOI: 10.1215/00703370-9624150
|View full text |Cite
|
Sign up to set email alerts
|

Family Policy Awareness and Marital Intentions: A National Survey Experimental Study

Abstract: Despite extensively examining the effects of family policies on marriage and fertility rates, previous research has paid little attention to the process of policy implementation and has implicitly assumed that individuals are fully aware of the policy information when making marital and fertility decisions. Challenging this assumption, we theorize policy awareness as an important mechanism for understanding the potential influence of family policies on individuals' marital intentions, an understudied yet cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(52 reference statements)
2
1
0
Order By: Relevance
“…Our results indicated that most of the reproductive-age population with two children, the target population of the three-child policy, had a low level of policy knowledge. Furthermore, participants who intended to have a third child showed a higher level of policy knowledge than those who did not intend to have a third child, which is consistent with the results of Gong and Wang’s study [ 24 ] on the association of family policy awareness and marital intentions in Japan. The failure of a family policy may be due to the policy itself but could also be attributed to low policy awareness and perceived accessibility among the target population [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results indicated that most of the reproductive-age population with two children, the target population of the three-child policy, had a low level of policy knowledge. Furthermore, participants who intended to have a third child showed a higher level of policy knowledge than those who did not intend to have a third child, which is consistent with the results of Gong and Wang’s study [ 24 ] on the association of family policy awareness and marital intentions in Japan. The failure of a family policy may be due to the policy itself but could also be attributed to low policy awareness and perceived accessibility among the target population [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, participants who intended to have a third child showed a higher level of policy knowledge than those who did not intend to have a third child, which is consistent with the results of Gong and Wang’s study [ 24 ] on the association of family policy awareness and marital intentions in Japan. The failure of a family policy may be due to the policy itself but could also be attributed to low policy awareness and perceived accessibility among the target population [ 24 ]. Thus, in addition to focusing on policy availability, policymakers should prioritize public awareness of the family policy.…”
Section: Discussionsupporting
confidence: 88%
“…This would lead to inferences on whether and how employees manage their time between work and family and how they may employ flexible work arrangements to accommodate fulfilling multiple roles. Another avenue for future research could be to study other family-supportive policies ( 52 ), besides flextime and flexplace, and how these other policies, such as civic participation, may moderate the relationship between time claims and burnout ( 53 ). In addition, although this research was conducted in the Netherlands, a developed country, the results in this study also hold significant implications for developing countries in terms of developing employee-friendly workplace policies.…”
Section: Discussionmentioning
confidence: 99%